Stability of the main resonance frequency of fricatives despite changes in the first spectral moment - Shadle, Christine H.; Chen, Wei-rong; Whalen, D. H. (The Journal of the Acoustical Society of America, 2016)
Spectral moments have been taken as the primary measurements of fricatives, but resonances are evident as well. To contrast the two, the X-ray Microbeam Database (XRMB) was used to investigate acoustic and articulatory behavior in [s] for 10 /sVd/ words and 9 /sCV*/ words for 24 subjects as in a previous study [Iskarous et al., JASA 129:2, 2011]. Spectral parameters were adapted from analysis of an acoustic corpus of adolescents’ [s] production [Koenig et al., JSLHR 56, Aug. 2013]. The time series of the frequency of the main resonance (FM) and the first spectral moment (M1) were compared to the constriction location estimated from the most anterior tongue pellet T1. FM quickly settles into a constant value largely determined by the position of T1; vowel context affects FM throughout [s] for some subjects. M1 however rises and then falls during [s], matching jaw-raising behavior (as estimated by the y-component of the jaw pellet) and correlated with an estimate of high-frequency energy. The results show that some aspects of the fricative acoustics behave differently over time and by context. It remains to be seen what the perceptual consequences of these differences are. [Work supported by NIH NIDCD-DC-002717.]